1976
DOI: 10.1029/eo057i004p00180
|View full text |Cite
|
Sign up to set email alerts
|

International deployment of accelerometers: A network for very long period seismology

Abstract: The value to seismology of a global net of seismometers has long been recognized. Indeed, the first proposal for such a net came in 1895, only 6 years after the discovery that earthquake waves could be recorded at long distances, and the first net of standardized instruments was in existence by 1898 [Dewey and Byerly, 1969; Wood, 1942; Milne, 1899]. A true network, involving not only standardized high‐quality instruments but also the exchange and ready availability of data, did not come until the establishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…The technical characteristics have been presented for stations are given in Table 1. They have been chosen so as the IDA network by Agnew et al (1976), for the GDSN to ensure a good spatial and also azimuthal coverage of the network by Peterson & Hutt (1982) and for the Indian Ocean. Fig.…”
Section: Data a N D General Scheme Of Processingmentioning
confidence: 99%
“…The technical characteristics have been presented for stations are given in Table 1. They have been chosen so as the IDA network by Agnew et al (1976), for the GDSN to ensure a good spatial and also azimuthal coverage of the network by Peterson & Hutt (1982) and for the Indian Ocean. Fig.…”
Section: Data a N D General Scheme Of Processingmentioning
confidence: 99%
“…• A differential pressure gauge [Cox et al, 1984] • A seismometer: Lacoste-Romberg gravimeter [Lacoste, 1967] -One vertical channel -Long period [Agnew et al, 1976] -Sample rate = 2 samples/sec à Nyquist frequency = 1 Hz -Levelled using motorized gimbals to within 5 x 10 -5 radians of a laboratorydetermined value -The centre value of uncertainty is approximately 1 x 10 -4…”
Section: : the Experimentsmentioning
confidence: 99%
“…Since we have no observation to infer the fault parameters L, W, D of the largest aftershock, we tentatively use an empirical relation among the fault parameters of shallow earthquakes (ABE, 1975;GELLER, 1976 (AGNEW et al, 1976) network and GDSN (Global Digital Seismic Network) are used in the waveform inversion for the Urakawa-Oki earthquake and its largest aftershock, respectively. The IDA and GDSN stations used in this study are shown in Fig.…”
Section: Analysis Of Crustal Deformationmentioning
confidence: 99%